The Effect of Emotional Intelligence and Work Environment on Organizational Citizenship Behaviour at Disdukcapil Surakarta - Habib Fajar Aditya; Agus Suyatno; Esti Dwi Rahmawati (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
Government agencies are organizations chosen to carry out state functions. The most valuable possession of any organization is the human resources employed in its activities. Human resource management is thus needed in the control and rationalization of the administration of human resources in an organization. Emotional intelligence refers to the capability to identify and know one's own emotions and feelings. The work environment, too, might affect employees in the demonstration of OCB. OCB refers to employee behavior beyond their routine activities. It involves displaying personal interest in fellow employees, giving suggestions for the better performance of fellow employees, and respecting and committing to the company. This study, therefore, aims at ascertaining the extent to which Emotional Intelligence and Work Environment influence the organizational citizenship behavior of Disdukcapil employees. The research design employed in this research is quantitative, with primary data sources. The sample used in this research includes all staff members from the Disdukcapil in Surakarta City. Data obtained by the researcher were analyzed using SPSS version 27. The results of this study conclude that emotional intelligence has a significant effect on OCB, work environment has a significant effect on OCB, and emotional intelligence and work environment both have a significant influence on OCB.